2012
DOI: 10.1152/japplphysiol.00802.2011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in H reflex and V wave following short-term endurance and strength training

Abstract: This study examined the effects of 3 wk of either endurance or strength training on plasticity of the neural mechanisms involved in the soleus H reflex and V wave. Twenty-five sedentary healthy subjects were randomized into an endurance group (n = 13) or strength group (n = 12). Evoked V-wave, H-reflex, and M-wave recruitment curves, maximal voluntary contraction (MVC), and time-to-task-failure (isometric contraction at 40% MVC) of the plantar flexors were recorded before and after training. Following strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 39 publications
6
110
2
Order By: Relevance
“…Thus, in addition to motoneuron excitability, the maximal firing frequency, as well as the proportion of motoneurons recruited will determine the size of the V-wave, as they will both affect the probability of antidromic collision. Although pre/postsynaptic inhibition may also affect the amplitude of the V-wave, these factors would influence the amplitude of the Hreflex similarly (Zehr 2006;Vila-Cha et al 2012). Interestingly, the reduction in V/M ratio was more than three times larger than the reduction in H/M ratio.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, in addition to motoneuron excitability, the maximal firing frequency, as well as the proportion of motoneurons recruited will determine the size of the V-wave, as they will both affect the probability of antidromic collision. Although pre/postsynaptic inhibition may also affect the amplitude of the V-wave, these factors would influence the amplitude of the Hreflex similarly (Zehr 2006;Vila-Cha et al 2012). Interestingly, the reduction in V/M ratio was more than three times larger than the reduction in H/M ratio.…”
Section: Discussionmentioning
confidence: 97%
“…This discrepancy suggests that the difference in V/M-ratio between young and elderly was mainly caused by the magnitude of efferent motor output, likely reflecting a reduced supraspinal descending drive in elderly. This indicates that the neural function may actually be more altered at supraspinal levels than at spinal levels (Aagaard et al 2002;Vila-Cha et al 2012). Such a central impairment may not immediately lead to a loss of muscle strength, since a gradual loss of motoneurons may be compensated for through axonal sprouting (McNeil et al 2005;Aagaard et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed a 20% increase in the amplitude of the H-reflex following the training. Furthermore, Vila-chã et al [59] compared the effect of a 3-week strength training and endurance training programme. They found that the amplitude of the H-reflex for the soleus muscle increased significantly among those persons who participated in strength training.…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%